Relationship between Circadian Phase Delay without Morning Light and Phase Advance by Bright Light Exposure the Following Morning - Michihiro Ohashi; Taisuke Eto; Toaki Takasu; Yuki Motomura; Shigekazu Higuchi (Clocks & Sleep, 2023)
Humans have a circadian rhythm for which the period varies among individuals. In the present study, we investigated the amount of natural phase delay of circadian rhythms after spending a day under dim light (Day 1 to Day 2) and the amount of phase advance due to light exposure (8000 lx, 4100 K) the following morning (Day 2 to Day 3). The relationships of the phase shifts with the circadian phase, chronotype and sleep habits were also investigated. Dim light melatonin onset (DLMO) was investigated as a circadian phase marker on each day. In the 27 individuals used for the analysis, DLMO was delayed significantly (−0.24 ± 0.33 h, p < 0.01) from Day 1 to Day 2 and DLMO was advanced significantly (0.18 ± 0.36 h, p < 0.05) from Day 2 to Day 3. There was a significant correlation between phase shifts, with subjects who had a greater phase delay in the dim environment having a greater phase advance by light exposure (r = −0.43, p < 0.05). However, no significant correlations with circadian phase, chronotype or sleep habits were found. These phase shifts may reflect the stability of the phase, but do not account for an individual’s chronotype-related indicators.